Phase transformation and mechanical properties of new bioactive glass-ceramics derived from CaO–P2O5–Na2O–B2O3–SiO2 glass system - Zhi Wei Loh, Zhi Wei Loh; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Awang Kechik, Mohd Mustafa; Yap Wing Fen, Yap Wing Fen; Mayzan, Mohd Zul Hilmi; Liza, Shahira; Wei Mun Cheong, Wei Mun Cheong (Elsevier, 2023)
This work investigates the role of sintering temperature on bioactive glass-ceramics derived from the new composition CaO–P2O5–Na2O–B2O3–SiO2 glass system. The sintering behaviour of the samples’ physical, structural, and mechanical properties is highlighted in this study. The experimental results indicated that the sintering process improved the crystallization and hardness of the final product. Results from XRD and FTIR showed the existence of carbonate apatite, pseudo-wollastonite, and wollastonite phases. From the results, the bioglassceramics sintered at 700 ◦C obtained the highest densification and optimum mechanical results. It had the value of 5.34 ± 0.21 GPa regarding microhardness and 2.99 ± 0.24 MPa m1/2 concerning fracture toughness, which falls in the range of the human enamel. Also, the sintered samples maintained their bioactivity and biodegradability after being tested in the PBS medium. The bioactivity does not affect but slows down the apatite formation rate. Overall results promoted the novel bioglass-ceramics as a candidate material for dental application.